Penyuluhan dan Pelatihan Pemanfaatan Limbah Perkebunan Kelapa Sawit Sebagai Sumber Energi Baru Terbarukan - Arief Suardi Nur Chairat; Lia Nur Octavia; Hendri Hendri; Ade Caswito; Dyah Pratiwi Kusumastuti; Tri Wahyu Oktaviani Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
At present energy sources are dominated by non-renewable materials which will run out over time, so it is important to introduce elements of society about renewable energy sources that can be obtained from the environment such as biomass from agricultural waste. Kampung Lantosan, Desa Gunung Bayu with a majority population of oil palm farmers as partners have not utilized organic waste when harvesting oil palm so that it accumulates and disturbs the comfort of the environment. PkM activities carried out in partner areas consist of counseling and training on the utilization of organic waste into energy. Through counseling and training activities regarding the processing of palm oil agricultural waste, partners have knowledge about the benefits of organic waste as an energy source and the ability to process organic waste into biopellets. The resulting biopellets are used as stove fuel or fuel in the gasification process to become syngas used by power plants. In addition to that, by utilizing the waste from oil palm agricultural crops, waste is reduced and the environment becomes cleaner.